The effect of wet coconut fibre on concrete properties (compressive strength and flexural strength) - Nur Ain , Hasan (2013)
Natural fiber is a fiber derived from plants or minerals. The use of fiber materials in the construction industry has been practiced all over the world. Ability of the engineering properties of the fiber has led to this study. This study was conducted to investigate the effect of using wet coconut fiber as an additive in concrete mix. Two types of testing were conducted in this study, compression test and flexural test. 48 samples were prepared in this study consist of 12 small beams with dimension of 100mm x 100mm x 500mm for flexural test and 36 cubes with dimension of 150mm x 150mm x 150nmi for compression test. Concrete with grade 25MPa was designed. Wet coconut fiber was added based on the percentage of concrete weight. In this study three different percentage of wet coconut fiber 5cm length was added into the concrete mix. The percentages are 0.1%, 0.2% and 0.3%. A control sample was used as a reference where all the results will compare it. Experimental results show that concrete mix added with wet coconut fibers. The result obtained indicate that the concrete added with 0.2% wet coconut fibers has the highest compressive strength compare with 0.1% and 0.3% but the strength is less than the control.